INFLUENCE OF QUINAPRIL ON THE REGULATORY-ADAPTIVE STATUS OF PATIENTS WITH CHRONIC HEART FAILURE HYHA CLASS I: RESULTS OF NOT COMPARATIVE STUDY - V. G. Tregubov; S. G. Kanorskiy; V. M. Pokrovskiy (Столичная издательская компания, 2015)
Aim. To assess effects of quinapril on the regulatory-adaptive status (RAS) in patients with chronic heart failure (CHF) NYHA class 1 and arterial hypertension (HT). Material and methods. Patients (n=49) with CHF NYHA class I and HT stage I-II (25 men and 24 women, aged 52.5±8.4 years) were included into an open noncomparative study. A cardio-respiratory synchronization (CRS) test, 6 minute walk test, treadmill test with evaluation of the maximal oxygen uptake during exercise, ambulatory blood pressure monitoring, echocardiography , determination of N-terminal prohormone of brain natriuretic peptide (NT-proBNP) plasma level were performed at baseline and after 6 months of quinapril therapy. Results. The quinapril treatment (average daily dose 17.3±7.9 mg) improved myocardium structural and functional parameters, increased the exercise tolerance, reduced neurohumoral activity , improved the RAS according to CRS test: increase in synchronization range of cardiorespiratory cycles per minute from 8.0±2.1 to 11.0±2.5 (Δ27.3%; p<0.01), as well as RAS index from 52.6±7.8 to 89.7±8.9 (Δ41.4%; p<0.01), and decrease in the duration of CRS development at the minimal border of cardiac cycles from 15.5±3.5 to 12.9±2.8 (Δ15.8%; p<0.01). Conclusion. Quinapril has a positive effect on the RAS in patients with CHF NYHA class I and HT of stage I-II.